Ten minutes ergometer rowing exercise increases pressure pain thresholds in high performance rowers - Simpson, A.I.; Pearson, Richard G.; Scammell, B.E. (JSciMed, 2016)
Background: Mechanical hypoalgesia has been demonstrated following bouts of acute exercise. The pain relieving properties of exercise thus have the potential to be utilised to help manage painful musculoskeletal conditions, such as osteoarthritis. The mechanisms that underlie this exercise - induced hypoalgesia are poorly understood; as is the type of exercise, the duration and the intensity required to produce hypoalgesia. A complete knowledge of these factors is required before therapeutic exercise programs for pain management can be implemented on an evidence basis in the clinical setting. This research provides a clearly defined exercise protocol which induces hypoalgesia. Hypothesis: Ten minutes ergometer rowing increases pressure pain thresholds in high performance rowers. Study design: Laboratory Study, within - group repeated measures Methods: 20 high performance rowers (13M:7F; mean age: 20.8 years ± 1.74) had pressure pain threshold measurements performed at three anatomical sites (2 local, 1 remote) before and immediately following 10 minutes ergometer rowing at 50-80% estimated VO2max. Results: Pressure pain thresholds were significantly increased (P < 0.05) at all anatomical locations post - exercise compared to pre - exercise. Conclusions: High intensity ergometer rowing induces statistically and clinically significant mechanical hypoalgesia at both local and remote sites in high performance rowers. Clinical relevance: Ergometer rowing is a low impact activity that may prove beneficial in the management of painful joint and muscle conditions, such as osteoarthritis.